(untitled) (NAWA: Journal of Japanese Studies, 2024)
This research aims to find out the process of the formation of the cosplay community and to find out the development of the cosplay community in Makassar City. In this research, the method used is an ethnographic method where the data used comes from interviews with informants. In the process of collecting data, the author gets from interviews with the founders of the cosplay communities. The results of this study show the process of the formation of the cosplay community in Makassar City and the development of the cosplay community in Makassar City. Members of the cosplay community are aware of the profit opportunities that exist when becoming a cosplayer. The community is only a place to express their hobby by gathering with people who have the same passion for cosplay. The cosplayers carry out their hobbies in cosplay while also running a business to gain profit and fame in the world of cosplayers in Makassar City.